1983
DOI: 10.1111/j.1464-410x.1983.tb03408.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Results of Optical Wrethrotomy

Abstract: In a 7-year period 137 men with urethral stricture underwent optical urethrotomy. Over 91% were relieved of their stricture symptoms and required no further treatment, including 41 patients in whom the follow-up period exceeded 4 years. The surgical technique is outlined. Strictures with the best prospect of cure were short and single. Optical urethrotomy is confirmed as the treatment of choice in strictures of the male urethra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…It should also be noted that DVIU is not free from complications. Although mostly published in the adult literature, complications from DVIU can be as high as 27% [11].…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that DVIU is not free from complications. Although mostly published in the adult literature, complications from DVIU can be as high as 27% [11].…”
Section: Discussionmentioning
confidence: 99%
“…The result of O.I.U. had been generally optimistic [2,3,4,5]. However, some studies have shown lower cure rate.…”
Section: Introductionmentioning
confidence: 99%
“…Η υποτροπή των στενωμάτων μετά εσωτ. ουρηθροτομία οφείλεται κυρίως στο βάθος της περιουρηθρικής ίνωσης και είναι γνωστό ότι το 15% των στενωμάτων θα υποτροπιάσουν μετά από οπτική ουρηθροτομή (25,26,31,32) και το πρόβλημα είναι να προβλεφθεί πιο στένωμα θα υποτροπιά σει μετά από κάποια ενδοσκοπική αντιμετώπιση (33,39,42).…”
Section: υπερηχοουρηθρογραφιαunclassified